The relationship between homocysteine and new-onset atrial fibrillation in patients with acute myocardial infarction - Ping Jin; Peng Wu; Juan Ma; Yitong Bian; Huijuan Kou; Xueping Ma; Shaobin Jia; Qiangsun Zheng (Annals of Medicine)
Objective Elevated homocysteine (Hcy) are linked to an augmented risk of cardiovascular disorders. However, relationship between Hcy and in-hospital new-onset atrial fibrillation (NOAF) among patients experiencing acute myocardial infarction (AMI) remains uncertain. This study investigated the association between Hcy and incidence of NOAF in patients with AMI.Materials and Methods We conducted a retrospective cohort study, involving 3,347 patients with AMI. Participants were categorized into tertiles on the basis of Hcy levels during admission, and the outcome was the incidence of NOAF. Logistic regression models were employed to explored the associations between Hcy and NOAF when adjusting for potential confounders. Non-linear relationships were explored using generalized additive models (GAMs) and threshold effect analyses. Stratified analyses were performed to explore the robustness and potential interaction effects of other clinical factors on Hcy-NOAF relationship.Results Higher Hcy were consistently linked with a greater likelihood of in-hospital NOAF across all models (OR: 1.03, p < 0.0001). GAM analyses revealed a nonlinear association with a steeper increase in NOAF risk at higher Hcy levels. Threshold effect analysis identified a turning point at 34.27 μmol/L and below this point the association between Hcy and NOAF was stronger. Stratified analyses indicated a stronger in patients with smaller left atrial anterior-posterior diameter (LAAD).Conclusion A nonlinear association has been identified between elevated Hcy and the likelihood of in-hospital NOAF among individuals diagnosed with AMI, particularly among those with smaller LAAD measurements.